Pastoral Pernikahan di Gereja Kemah Injil Indonesia Daerah Sintang dalam Perspektif Kristen - Mustakim (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Gereja Kemah Injil Indonesia implements holy marriages and Christian marriages and in it pastoral care is needed so that marriage services can be carried out according to God's Word and Church regulations. Pastoral services or pastoral care that will be discussed in this section, are not pastoral care that has been implemented in the Sintang GKII, because the Sintang GKII does not yet have standard pastoral care for prospective couples who will marry in the church. Couples who do not meet the requirements of "Holy Marriage" according to GKII regulations can choose to marry with the type of "Christian Marriage" where on average each couple is married without prior premarital guidance. The methodology of this research is historical research by conducting direct interviews with key informants as eye witnesses of historical events. Through this research, we will explore history so that it can be a lesson for the next generation. Pastoral Marriage at GKII Sintang in a Christian Perspective is a form of service in the form of an evaluative descriptive study on the pastoral implementation of marriage, both premarital and pastoral in marriage. May it be able to contribute to pastors and church leaders in carrying out pastoral care at marriage.